Novel Microorganisms Contribute to Biosulfidogenesis in the Deep Layer of an Acidic Pit Lake - Ayala-Muñoz, Diana; Burgos, William D.; Sánchez-España, Javier; Falagán, Carmen; Couradeau, Estelle; Macalady, Jennifer L. (Frontiers in Bioengineering and Biotechnology, 2022)
Cueva de la Mora is a permanently stratified acidic pit lake with extremely high concentrations of heavy metals at depth. In order to evaluate the potential for in situ sulfide production, we characterized the microbial community in the deep layer using metagenomics and metatranscriptomics. We retrieved 18 high quality metagenome-assembled genomes (MAGs) representing the most abundant populations. None of the MAGs were closely related to either cultured or non-cultured organisms from the Genome Taxonomy or NCBI databases (none with average nucleotide identity >95%). Despite oxygen concentrations that are consistently below detection in the deep layer, some archaeal and bacterial MAGs mapped transcripts of genes for sulfide oxidation coupled with oxygen reduction. Among these microaerophilic sulfide oxidizers, mixotrophic Thermoplasmatales archaea were the most numerous and represented 24% of the total community. Populations associated with the highest predicted in situ activity for sulfate reduction were affiliated with Actinobacteria, Chloroflexi, and Nitrospirae phyla, and together represented about 9% of the total community. These MAGs, in addition to a less abundant Proteobacteria MAG in the genus Desulfomonile, contained transcripts of genes in the Wood-Ljungdahl pathway. All MAGs had significant genetic potential for organic carbon oxidation. Our results indicate that novel acidophiles are contributing to biosulfidogenesis in the deep layer of Cueva de la Mora, and that in situ sulfide production is limited by organic carbon availability and sulfur oxidation.